FINANCIAL ASPECTS OF INNOVATIVE DEVELOPMENT - Світлана Заїка; Олександр Грідін; Олена Заїка (Економіка та суспільство, 2023)
Innovation is a key factor in economic growth and competitiveness. It enables businesses to create new products and services, which increases their efficiency and profitability. However, innovation is costly. It requires significant financial resources, which are not always available to enterprises. This is one of the main problems hindering the innovative development of the economy. The purpose of this article is to study modern approaches to financing innovations, identify the factors that influence the choice of financing sources, identify existing problems, and develop proposals for their solution. The article examines the main sources of financing innovations, which include budget financing, company’s own funds, and attracted and borrowed funds. It argues that effective financing of innovative activity requires a comprehensive approach that takes into account both internal and external factors. Solving the problems of financing innovations and increasing the efficiency of innovative projects is an important task for increasing the competitiveness of the economy. For the successful development of innovations, it is necessary to create a favorable environment for financing and develop effective mechanisms for evaluating the effectiveness of innovative projects. Solving the problems identified during the research will help increase the level of innovative activity in the country and contribute to the growth of its competitiveness.